P257 A comparison of scoring systems in the management of a range of pulmonary embolism patients in a university hospital. (16th November 2010) - Maruthappu, M; Manuel, A; Christian, A; Hollington, A; Ramsden, M; Alexopoulou, Z; Healy, M; Giles, M
Abstract : Introduction: Pulmonary embolism (PE) is a leading cause for inpatient admission and in patient mortality in the UK. Its clinical features are often nonspecific, making a diagnosis of pulmonary embolism difficult and without appropriate treatment; a pulmonary embolism can be fatal. We compared three scoring systems (Geneva and Wells score, which are both predictive tools and Pulmonary Embolism Severity Index (PESI) a risk stratification tool) in three distinct patient groups; those whose primary cause of death was pulmonary embolism, those whose management required admission or patients managed on an outpatient basis. Methods: A retrospective review of case notes for patients with the primary diagnosis of pulmonary embolism from 2009 to 2010 was performed at the Oxford Radcliffe NHS Trust, applying the Wells, PESI and Geneva scoring systems. Death from PE was defined by the presence of a PE or it being listed as the primary cause of death on the death certification in combination with concordant view of a senior clinician of the medical team. Outpatient management was based on patients having a zero length-of-stay. All groups were distinct. Results: See Abstract P257 Table 1 for selected results. Discussion: Across all our group of patients, the PESI outperformed both the Wells and Geneva score. Patients who died from PE were older and more hypoxic, and often caused most diagnostic difficulty presenting with non-respiratory symptoms in over half of the cases. Abnormal chest radiograms were common in all groups and although Ddimer assists in diagnosis other biomarkers such as troponin and BNP were not helpful. The PESI also outperformed the other scores as aid on deciding to manage patients with PE as an outpatient, but still with a degree of uncertainty. In conclusion, PESI should be considered in the management and risk stratification of PE and PE should be always considered in older patients with non specific clinical features, abnormal radiology and hypoxia. Managing PE as an outpatient potentially requires a combination of scoring systems in a prospective study.